VD_FINDINFO HC / 2011 / 74 vom 15. Februar 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, RÉSILIATION IMMÉDIATE, DEMEURE DU DÉBITEUR, SOMMATION, POUVOIR D'EXAMEN LIMITÉ, EXPULSION DE LOCATAIRE, NULLITÉ | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 457 al. 1 CPC, 457 CPC, 23 al. 2 LPEBL, 23 LPEBL, 27 al. 2 LPEBL, 405 al. 1 CPC (CH)